The Effect of using Picture Strip Story on Students’ Speaking Skill - Eva Christina Turnip; Ades Pranata Purba; Eva Natalia Sitompul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This research was conducted at SMP YayasanPangeranAntasari, which located in Jl. Veteran No. 1060/19 Helvetia, Medan, North Sumatera. The data were collected by using a speaking test using pieces of pictures in narrative texts as the media. The results show the picture strip story has a positive effect on students' speaking skills through improving the students' speaking scores. This subject of this research were the students at the second grade A. This research was conducted by researchers starting with giving the pre-test to know the students' speaking ability before conducted the post-test in the last meeting, researchers treat the students using the picture strip story. This study shows the significant effect of using PST has a positive effect on students' speaking skill through the improvement of students' speaking scores. It was proven by the means in Post-test was higher than in Pre-test (73,55- 48,00). The t.obs>t.table (P = 0,05), df(19). It means that Ha was accepted. Through the scores between Pre-test and Post-test shows a significant difference after being taught using the PST. Therefore, PST is one of some media which can be used to improve the students' speaking skill. Keyword: Picture Strip Story, Speaking Skill, Effect.